Turning a new page in Georgia's history - Darejan Daduna Khutsishvili (IBSU Scientific Journal (IBSUSJ), 2010)
After the demise of the USSR, Georgia has become geopolitically a key state in the Southern Tier region, which connected the landlocked, but rich with mineral resources region with theWest by gas and oil pipelines. Georgia has become one of the places, where the interests of powerful states collide. Therefore, Georgia had to find means of securing its independence and territorial integrity and reluctantly became a member of the Commonwealth of Independent States. Russia took advantage of NATO's disunity and tried to foil Georgia's path to membership. The Russo-Georgian War shocked international community but it also With outsourcing the diplomatic lead in Russo-Georgian War to the European Union, the United States wanted to show Russia how the EU and other parts of the world were united against Russia's attack on a sovereign country. The true reason of Russo-Georgian war, was to claim nineteen-century-old style Russian sphere of influence in the Southern Tier region, the region which is a natural conjuncture of the eastern and western parts of Eurasia, thus geostrategically vital for the EU itself.Without independent Southern Tier region the EU will be depended on the Empire, under whose control these regions fall.
Keywords: 330; Russo-Georgian war; Georgia; independence and territorial integrity; NATO membership